2020
DOI: 10.1016/j.vacuum.2020.109358
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electronic properties of graphitic carbon nitride (g-C3N4) under biaxial strain

Abstract: Using the first-principles density functional theory calculations, we investigate the mechanical and electronic properties of biaxially strained graphitic carbon nitride (g-C 3 N 4 ). The results show highly isotropic mechanical properties and large linear elasticity of g-C 3 N 4 . Moreover, both the Perdew-Burke-Ernzehof (PBE) and Heyd-Scuseria-Ernzerhof (HSE06) band gaps reach the maximum values at 10% strain. The bonding properties are analyzed based on the electronic localization function (ELF). In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 48 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…As is well known, strain modulation is an effective way to alter the electronic properties of 2D vdW heterostructures [ 52 , 53 , 54 ]. In this work, we applied the in-plane biaxial strain to the SiS 2 /WSe 2 hetero-bilayer by changing the lattice constant of the system in both the x and y directions (i.e., compressive or tensile stresses).…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, strain modulation is an effective way to alter the electronic properties of 2D vdW heterostructures [ 52 , 53 , 54 ]. In this work, we applied the in-plane biaxial strain to the SiS 2 /WSe 2 hetero-bilayer by changing the lattice constant of the system in both the x and y directions (i.e., compressive or tensile stresses).…”
Section: Resultsmentioning
confidence: 99%
“…The ultimate stress, ultimate strain, Young's modulus, and Poisson's ratio of C 4 N 4 and other 2D materials are compared (Table 1). Through comparison with graphene (17 %, 34 N m À 1 ), [56] C 2 N (12 %, 32 N m À 1 ), [57] g-C 3 N 4 (10 %, 59.27 N m À 1 ), [58] we can conclude that the C 4 N 4 monolayer is flexible because of its lower ultimate stress and similar ChemSusChem ultimate strain. Interestingly, the C 4 N 4 monolayer shows the anisotropic Young's modulus and Poisson's ratio, which may facilitate application in direction-dependent devices.…”
Section: Mechanical Propertiesmentioning
confidence: 86%
“…It is interesting to note that by adjusting the N/C ratio and moving the N and C atoms around in the lattice structure, the electric characteristics of carbon nitride nanosheets can be flexibly designed to range from half-metal to semiconductor [ 60 , 61 ], offering insightful design guidance for novel g-C3N4-based two-dimensional elastic electrical and spintronic devices. Biaxially strained graphitic carbon nitride’s (g-C3N4) mechanical and electrical characteristics were studied by Qu L.-H. and colleagues [ 62 ]. The results demonstrated that g-C3N4 has substantial linear elasticity and extremely isotropic mechanical characteristics.…”
Section: Applicationsmentioning
confidence: 99%